EFFECT OF HOLDING TIME AND COOLING RATE ON THE MICROSTRUCTURE OF RENE 142 SUPERALLOY - Raihan Renando, Ghiffary
Nickel-based superalloys are the material used for turbine blades in airplane engines as they are designed to withstand creep. Consequently, gamma prime precipitates within the microstructure of these alloys will change in shape and size that will affect its operational lifetime. Thus, heat treatment is done to optimize gamma prime morphology. A used 30000-hour nickel-based superalloy, Rene 142, has been solution heat treated at 1250°C with 30-minute and 60-minute holding time as well as cooling in air and furnace. Electro-etching is done to the specimens to observe ?’ during Field Emission Scanning Electron Microscopy before measuring its width, height, area, and area fraction using ImageJ software. From those microstructure images and data from image analysis, the main phenomena that took place were dissolution, nucleation, growth and coarsening of gamma prime. It can be obtained that under a longer holding time before air cooling, gamma prime size will become smaller and spherical but if furnace cooling is used, its size will become bigger but still cuboidal. Its average area fraction will not be affected. When holding time is constant and cooling rate is decreased, the gamma prime size will become bigger, more cuboidal and its area fraction increases. If this experiment is related to overheating, it can be predicted to decrease the Rene 142 creep properties if it exceeds the 30-minute holding time before air cooling condition.